Boosting catalyst activity in cis-selective semi-reduction of internal alkynes by tailoring the assembly of all-metal aromatic tri-palladium complexes. Issue 40 (11th July 2016) - Monfredini, Anna; Santacroce, Veronica; Deyris, Pierre-Alexandre; Maggi, Raimondo; Bigi, Franca; Maestri, Giovanni; Malacria, Max
Abstract : Zwitterionic all-metal aromatic tri-palladium complexes can catalyse the cis -selective semi-reduction of internal alkynes at ppm levels. Abstract : Highly symmetric [Pd3 ] + clusters that present delocalized metal–metal bonds can catalyse the selective semi-reduction of internal alkynes to cis -alkenes. Studies on factors governing the formation of all-metal aromatics enabled the design of an optimised catalytic system that delivers cis -alkenes with almost complete selectivity on a gram scale with very low catalyst loadings (0.03 mol%).